Inhibition of HMGB1 improves necrotizing enterocolitis by inhibiting NLRP3 via TLR4 and NF‐κB signaling pathways. Issue 8 (7th January 2019) - Yu, Renqiang; Jiang, Shanyu; Tao, Yaqin; Li, Ping; Yin, Juan; Zhou, Qin
Abstract: Objective: To explore the relationship between high‐mobility group box 1 (HMGB1) and NLR pyrin domain containing 3 (NLRP3) in the development of necrotizing enterocolitis (NEC). Methods: NEC rat models were constructed and treated with HMGB1 inhibitor glycyrrhizin (GL) with different concentration. An inflammatory condition of intestinal tissue in newborn NEC rats was observed by hematoxylin and eosin staining. The messenger RNA (mRNA) and protein expression of HMGB1, NLRP3, toll‐like receptor 4 (TLR4), nuclear factor‐κB (NF‐κB), and caspase 1 were determined by real‐time polymerase chain reaction and western blot analysis, respectively. The content of interleukin (IL)‐1β and tumor necrosis factor‐α (TNF‐α) was determined by enzyme‐linked immunosorbent assay. Human intestinal epithelial cell lines were induced to NEC by lipopolysaccharides (LPSs). LPS‐induced cells were transfected with small interfering RNA‐HMGB1 and NLRP3 plasmid vector. The mRNA and protein expression of HMGB1, NLRP3, TLR4, NF‐κB, caspase 1, IL‐1β, and TNF‐α were determined by real‐time PCR and western blot analysis, respectively. Results: The mRNA and protein expression of HMGB1 and NLRP3 in the NEC group was significantly higher than the control group. Inhibition of HMGB1 expression improved intestinal inflammation in newborn NEC rats. The expression of HMGB1, NLRP3, TLR4, NF‐κB, and caspase 1 was upregulated in NEC and was weakened after treating with GL. LPS induction to intestinal epithelial cells markedly increased the expression of HMGB1, NLRP3, TLR4, NF‐κB, caspase 1, IL‐1β, and TNF‐α. The knockdown of HMGB1 abolished the increase of expression, whereas further transfection with NLRP3 plasmid vector recovered the increase. Conclusion: HMGB1 and NLRP3 were all upregulated in the development of NEC. Inhibition on HMGB1 could improve the intestinal inflammation in NEC by inhibiting NLRP3 via TLR4 and NF‐κB signaling pathways. Abstract : High‐mobility group box 1 (HMGB1) and NLR pyrin domain containing 3 (NLRP3) were all upregulated in the development of necrotizing enterocolitis (NEC). Inhibition on HMGB1 could improve the intestinal inflammation in NEC by inhibiting NLRP3 via toll‐like receptor 4 and nuclear factor‐κB signaling pathways.